MOLECULAR IDENTIFICATION AND PHYLOGENETIC ANALYSES OF ECTOPARASITES AND ECTOSYMBIONTS THAT INFECT BLUE SWIMMING CRABS (PORTUNUS PELAGICUS) - Heirina, Anna; Murtini, Sri; Neksidin (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
The decline in blue swimming crab populations can be caused by overfishing and several factors of the aquatic environment, such as anthropogenic pollution, water quality and the presence of ectoparasite in the crab. Molecular studies are essential to validate a particular species of ectoparasites and ectosymbionts that infect Crab. A total of 143 crabs were sampled from fishermen in Demak, Muara Gembong and Labuhan Maringgai. Six ectoparasite and ectosymbionts species, Chelonibia testudinaria (Crustacea), Dianajonesia tridens (Crustacea), Octolasmis angulata, O. warwicki (Crustacea), Ostrea puelchana (Mollusca) and Thompsonia sp. (Crustacea) were isolated. Three ectoparasite and ectosymbionts species that were successfully validated based on the COI mtDNA genes were C. testudinaria, D. tridens, Oc. angulata. Validation of isolated ectoparasites infecting P. pelagicus was performed using the mtDNA marker COI gene to identify three ectoparasite species molecularly, namely C. testudinaria, D. tridens, and Oc. angulata. The results of the five sample analyses of ectoparasites based on the number of specific nucleotide sites in each sample show that the suspected species C. testudinaria, D. tridens and Oc. angulata had missense mutations.